Some Calabrian stones as building materials: characterization, durability and use suggestions - Forestieri, Giulia; Pantano, Pietro Salvatore; Ponte, Maurizio; Campolongo, Alessandro; De Francesco, Anna Maria; De Buergo Ballester, Mónica Alvarez (My University, 2017)
The aim of this PhD thesis is to provide new scientific data regarding the use of certain Calabrian stones as building materials. This investigation included specific local stones used by the most important schools of Stonemasons of Calabria, in particular in the Cosenza Province; focusing on how properties of different building materials have influenced the figurative and architectural models. In this study, stones commonly used as building materials are selected according to two important criteria: 1. The large employment of these materials in the past as building and decorative elements. Studying the use of selected stones in the centuries assists in identifying four lithotypes largely used by the most important Calabrian Schools of Stonemasons in the Cosenza Province: • San Giovanni in Fiore granite - in the Sila area by the school of San Giovanni in Fiore and famous for its severe style due to “Joachim of Fiore” rules, and to material hardness. • Grisolia stone – known as “gold stone” for its gold inclusions; limestone that represents the principal building material of the majority of the historical centers of the northern Tyrrhenian part of the Calabrian region and a small part of the Basilicata region. • San Lucido stone - biocalcarenite known in the past as “biancolella”; employed as a building material in the historical center of San Lucido and in the historical center of Cosenza, to build structural and decorative elements such as portals and arches. • Fuscaldo stone - sandstone commercially known as “sweet stone” and utilized by artisans of the 14th century school of Fuscaldo; principally known for the construction of portals of noble palaces, built in the Spanish “plateresco” (plateresque) style for ornamental elements. 2. Lithotypes belonging to the different active and non-active important quarry areas of the Cosenza Province. Also taken into account is the possibility that these quarries may still be exploited for a local limited use, or a possible diffusion on a large scale out of the Region. Special attention is dedicated to the characterization, durability, and to the building techniques employed in the past of the selected stones. The petrophysical and mechanical characterization of these stones are performed by means of studying the petrographic characteristics, chemical and mineralogical composition, hydric properties; and the physical and mechanical behavior, with special attention to possible anisotropies. For this purpose, laboratory and non-destructive tests on quarry samples complying the current standards for “natural stones” and for the “conservation of cultural property” are performed. Salt crystallization and freeze-thaw tests are performed to assess the durability of the stones and to relate the investigated stone properties with their behavior towards decay agents. Among all the investigated lithotypes, San Giovanni in Fiore granite and Grisolia stone result the stones with a better mechanical and resistance behavior than the other lithotypes. In terms of durability, they are the most durable stones, and in terms of mechanical strength resistance, the strongest stones, both suitable for indoor and outdoor uses. But, petrographically, in the case of San Giovanni in Fiore granite, the oriented sets of microcracks demonstrate that microcracks influence the physical and mechanical behavior of this lithotype. In fact, comparing San Giovanni in Fiore granite with other similar granites, this stone presents worse properties and an anisotropic strength behavior, connected to the different orientation of its intracrystalline and intercrystalline microcracks. San Lucido calcarenite is classified as a stone with better mechanical features than petrophysical and hydric properties, so, the recommended use is for structural purposes, especially inside rather than for ornamental and external uses, in general where salts are not present. Concerning both petrohysical-mechanical properties and durability, Fuscaldo sandstone is the stone with the worst behavior, if compared with the other investigated lithotypes. Its mineralogical composition connected to the susceptibility of some minerals, its high open porosity, the presence of a lot of micropores, its anisotropic hydric behavior, the high degree of ultrasonic anisotropy and its low mechanical strengths, makes this stone sensitive to decay processes and the recommendation is to use this stone for inside purposes and where no salts are present. Results demonstrate that anisotropy and porosity are the main influencing factor in the stone behavior and durability. The way in which stones are positioned can avoid decay processes and improve their petrophysical-mechanical properties. In particular, it is suggested positioning the most anisotropic lithotypes (e.g. Fuscaldo sandstone) with the Z-direction parallel to the loading direction to obtain higher strengths and, simultaneously, to minimize water absorption. Moreover the pore structure, the pore-size distribution, the open porosity and the hydric behavior influence directly the stone resistance in front of decay agents. Microporous stones (e.g. Fuscaldo sandstone) or stones with high capillary coefficients (e.g. San Lucido calcarenite) have been classified as more susceptible to decay agents. Furthermore, an attempt is made to consider possible modifications of current standards and performed non-destructive techniques, strictly focusing on the applied methods and the tested material of this research. In conclusion, all obtained results indicate the optimum use and the best methodology to perform, for the four investigated stones as building materials with regards to the stones’ properties and with particular attention to different behaviors towards the anisotropy
Dottorato di Ricerca in Scienze e Ingegneria dell’Ambiente, delle Costruzioni e dell’Energia-SIACE. Ciclo XXIX
Keywords: Engineering geology; Building stones